2013
DOI: 10.1007/s00277-013-1765-6
|View full text |Cite
|
Sign up to set email alerts
|

Induction of molecular remission by using anti-CC-chemokine receptor 4 (anti-CCR4) antibodies for adult T cell leukemia: a risk of opportunistic infection after treatment with anti-CCR4 antibodies

Abstract: The CC-chemokine receptor 4 (CCR4) is expressed in almost ATLL cells. Thus, anti-CCR4 antibodies can be used as a treatment strategy for ATLL. Mogamulizumab (MOG), which is a defucosylated anti-CCR4 monoclonal antibody, showed good results even in patients with recurrent ATLL in phase I or II studies. We treated 8 elderly patients with ATL who were resistant to chemotherapy using MOG monotherapy. All patients received 1.0 mg/kg of mogamulizumab (MOG) once per week for 8 weeks by intravenous infusion. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The efficacy of mogamulizumab in the treatment of CCR4-negative solid cancers, where Treg depletion is desirable, is currently being assessed. A recent report outlining the treatment of four elderly patients with mogalizumab has also suggested that an additional side-effect may be the risk of opportunistic infection with cytomegalovirus ( Ohyama et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of mogamulizumab in the treatment of CCR4-negative solid cancers, where Treg depletion is desirable, is currently being assessed. A recent report outlining the treatment of four elderly patients with mogalizumab has also suggested that an additional side-effect may be the risk of opportunistic infection with cytomegalovirus ( Ohyama et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been some reports describing opportunistic viral infection after mogamulizumab therapy for patients with ATL, such as cytomegalovirus infection ( 8 , 9 ), reactivation of hepatitis B virus ( 10 ), and fatal pneumonia and viremia due to parainfluenza virus ( 11 ). Indeed, fatal cytomegalovirus pneumonia after mogamulizumab therapy was reported in a patient with T-cell lymphoma other than ATL ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rituximab decreases the number of normal CD20-positive cells (9), while alemtuzumab causes lymphocytotoxic immunosuppression through the suppression of T-cell function and decrease in the number of CD4 cells (10). Ohyama et al described that 2 of 4 patients with ATLL who underwent mogamulizumab therapy developed CMV infection (11). Two patients with CMV infection achieved molecular CR.…”
Section: Discussionmentioning
confidence: 99%